THE EFFECT OF THE COMMUNICATIVE APPROACH ON IMPROVING ARABIC GRAMMAR COMPREHENSION AMONG 12TH-GRADE STUDENTS AT MA NAHDLATUL SHAUFIAH WANASABA - Zakaki (Journal of Education, Teaching, and Learning, 2024)
This study investigated the effect of the communicative approach on improving Arabic grammar comprehension among 12th-grade students at MA Nahdlatul Shaufiah Wanasaba. The primary aim was to evaluate whether this teaching method enhanced students' understanding of Arabic grammar more effectively than traditional methods. The research employed a quantitative method with a quasi-experimental design, involving two groups: an experimental group taught with the communicative approach and a control group instructed using conventional methods. The sample consisted of 47 students selected through purposive sampling. Data were collected using pre-tests and post-tests to measure grammar comprehension before and after the intervention. The results showed that the experimental group exhibited a significant improvement in grammar understanding, with an average score increase of 14.7 points, compared to a 5.4-point increase in the control group. This significant difference demonstrated the effectiveness of the communicative approach in engaging students and enhancing their practical application of language skills. The findings suggested that this approach not only improved students' grammar comprehension but also encouraged active participation in learning, making it a beneficial tool in language education. Furthermore, this study's results highlighted the potential for communicative methods to be integrated into Arabic language instruction to improve overall educational outcomes. Future research should explore the broader applicability of this approach, particularly in different school settings and over a longer period. This study made a valuable contribution to the field by showcasing the effectiveness of innovative teaching strategies in enhancing language acquisition.